Vulnerability of family farming systems to climate change: The case of the forest-savannah transition zone, Centre Region of Cameroon - Pierre Marie Chimi; William Armand Mala; Karimou Ngamsou Abdel; Jean Louis Fobane; François Manga Essouma; John Hermann Matick; Eusebe Yldephonse Nyonce Pokam; Imma Tcheferi; Joseph Martin Bell (Research in Globalization, 2023)
Family farms are especially vulnerable to the negative effects of climatic variations and changes. In this regard, this paper assessed the factors that influence family farmers' vulnerability to climate variability and change in the transition zone between forest and savannah in the northern part of the Centre Region of Cameroon. The study did this by combining primary data (gathered from a survey of 180 smallholder farmers) with secondary data (information on temperature and rainfall). Field observations were also conducted on these family farms in Mbangassina, Ntui, Batchenga, and Obala from January to March 2020, March to May 2021, and July to September 2021. We used statistical tools for both descriptive, multivariate and inferential analyzes. Small farmers have faced the highest temperatures and heat waves. Everybody living in this community is exposed to the same temperatures and heat waves. Maybe smallholder farmers are susceptible or vulnerable to these heat waves and high temperatures. Extreme droughts, which are becoming more often, and diminishing rainfall totals were assumed to be the key contributors to climate sensitivity. According to the findings, family farms in Obala are just marginally vulnerable to climatic variability and change (1.1 vulnerability score), whereas those in Batchenga, Ntui, and Mbangassina have considerable vulnerability indices (2.16, 2.17, and 2.99 vulnerability scores respectively). A significant noncausal correlation exists between vulnerability and four and five continuous and discontinuous explanatory factors, respectively. The binomial logistic regression model demonstrates statistically significant inverse causal links between five of the six explanatory factors and the sensitivity of family farmers to climate change. According to the model, useful agricultural area (Ø = -0.348, p < 0.0001), soil fertility (Ø = -0.568, p < 0.05), Dioscorea spp. (Ø = -0.926, p < 0.05), precipitation during these 10 to 30 years (Ø = -0. 582, p < 0.05), and annual income (Ø = -0.002, p < 0.01) all contributed to lessening smallholder farmers' vulnerability to unfavorable climate variability and change. The drought variable has a significant positive causal relationship. This leads to the conclusion that these six explanatory variables largely impact smallholder farmers' vulnerability to climate fluctuation and change. According to the study's conclusions, family farmers should be given more financial help and reliable climatic information to reduce their vulnerability to climate fluctuation and change.
Keywords: 330; Climate variability and change; Family farmers; Farming system; Forest-savannah transition zone; Vulnerability